Hydrothermal performance of microchannel heat sink integrating pin fins based on triply periodic minimal surfaces - Ahmed Raafat; Moza Alteneiji; Mohamed Kamra; Saeed Al Nuaimi (Case Studies in Thermal Engineering, 2025)
The increasing demand for high cooling performance and low power consumption in microchips has driven research toward microchannel heat sinks. Previous studies have explored attaching pin fins with conventional shapes, such as square pin fins, to increase surface area for enhanced cooling. However, this approach often comes at the cost of higher pressure drop and reduced efficiency. In this work, triply periodic minimal surfaces are investigated as pin fins for microchannels. These structures offer a high surface area-to-volume ratio, targeting high Nusselt numbers, while their porous-like topology reduces channel blockage, achieving balanced hydrothermal performance. A numerically validated model, supported by experimental data from literature, is employed to study and analyze three lattice based pin-fin designs, namely: the IWP pin fin, Hybrid A pin fin, and Hybrid B pin fin. The results show that the novel hybrid designs, which combine both square pin fins and the I-graph wrapped package-graph (IWP) lattice at their core, achieve a 54% reduction in pressure drop without compromising thermal performance, as indicated by average Nusselt numbers and maximum temperatures, compared to conventional square pins. Additionally, a 27% improvement in thermal efficiency was observed. This comprehensive study demonstrates the influence of triply periodic minimal surface structures on generating secondary cooling flows and disrupting thermal boundary layers. Finally, the findings encourage further exploration of other lattices, such as Gyroid and Diamond structures, which are expected to exhibit similar trends.